SIMULATION OF FATIGUE CRACK INITIATION LIFE OF TC4 TITANIUM ALLOY BASED ON ITS MESOSCOPIC PROPERTIES - JIANG Ze; XU XiWu; GUO ShuXiang; WU Bin; QI Yan (Jixie qiangdu)
This paper presents that the prediction model of fatigue crack initiation life of TC4 titanium alloy,and the feasibility of the model in predicting the fatigue crack initiation life of TC4 titanium alloy is verified by experiments. Based on the micro dislocation model of crack initiation and Tanaka mura’s formula of crack life,considering the surface roughness,a finite element model for fatigue crack initiation of TC4 titanium alloy is proposed,and the validity of the simulation model is verified by experiments. The results show that the crack initiation forms of the model are different under different load levels. At high stress levels,the model has a large number of independent microcracks in addition to the initiation and propagation of the main cracks,with a large crack density. At low stress levels,the model has a small number of independent microcracks,with a small crack density.